Analisa Pemilihan Supplier Bahan Baku Pasir Pada Industri Beton Dengan Metode Integrasi AHP dan TOPSIS. - Muhammad Prasha Risfi Silitonga (Rekayasa Sipil, 2019)
Infrastructure progress in Indonesia today has affected the construction industry, one of which is concrete. The high demand for concrete as a major component of development has made these industrial suppliers have performance and capability to demand. PT XYZ is a ready mix and precast company that has problems in the procurement of fluctuating sand material and does not meet the target in 2017, due to supplier performance so that suppliers need to be selected with certain criteria. This study examined the criteria and preference values of the five selected suppliers (PT CAS, CV KK, PT PAP, PT APP and PT TTJ) using the AHP and TOPSIS methods. In the first step we tested the weight between the criteria, then tested the weight between the sub-criteria with the AHP method. Then tested the value of the preference of the TOPSIS method by weighting the results of the determination by AHP. From the results of this study the results obtained from the AHP method that quality has the largest criteria weight with a value of 0.29, besides the sub-criteria with the largest weighting criteria is the history of corporate cooperation with a value of 0.56. Whereas the supplier with the largest preference value with the TOPSIS method is PT TTJ with a preference value of 0.69.